О зависимости выхода люминесценции от размера дисперсной среды - Горячев Б. В. Борис Валентинович; Ларионов В. В. Виталий Васильевич; Могильницкий С. Б. Сергей Борисович; Савельев Б. А. (Томск, 1985)
Деп. в ВИНИТИ 29.12.85, № 9029-В